Efficacy and Safety of Remimazolam for Procedural Sedation: A Meta-Analysis of Randomized Controlled Trials With Trial Sequential Analysis - Jhuang, Bo-Jyun; Yeh, Bo-Han; Huang, Yen-Ta; Lai, Pei-Chun (Frontiers in Medicine, 2021)
Background: Remimazolam is a new ultrashort-acting benzodiazepine. Remimazolam has been approved for procedural sedation by the US Food and Drug Administration in 2020. However, prior trials and the participants they enrolled were limited. Aim: In this meta-analysis, we investigated the effectiveness and adverse events (AEs) of remimazolam during procedural sedation. Materials and Methods: The study protocol was registered (DOI: 10.37766/inplasy2020.8.0043), and six databases were searched. We performed meta-analysis, trial sequential analysis (TSA), and Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology for judging the certainty of evidence (CoE). Results: A total of five randomized controlled trials with 1,248 participants were included. Compared with the use of midazolam, the utilization of remimazolam resulted in an increase in procedure success rate (odds ratio [OR] = 9.01, 95% confidence interval [CI]: 2.35–34.57), a reduction in the application of rescue medication (OR = 13.58, 95% CI: 3.46–53.28), a decrease in time to recovery (minutes, weighted mean difference [WMD] = −5.70, 95% CI: −8.68–−2.72), and a better cognitive recovery of Hopkins Verbal Learning Test-Revised (WMD = 5.22, 95% CI: 2.88–7.55). No difference was found in completion of procedure (OR = 1.68, 95% CI: 0.72–3.90) with inconclusive in TSA. Despite no difference of total AEs (OR = 0.60, 95% CI: 0.24–1.50), more detailed analysis of AEs remained inconclusive in TSA. The GRADE assessment demonstrated low to very low CoE. Conclusion: Our analysis suggested that remimazolam may be a better choice for procedural sedation than midazolam. Nevertheless, further studies are warranted to conclusively establish its safety.